THE PROBLEM OF MANDATORY REPLACEMENT OF PUNISHMENT TO MORE SEVERE ONE - V. M. Stepashin (Правоприменение, 2018)
The subject. The article deals with the problem of mandatory replacement of punishment, not related to imprisonment, with more stringent measures of state coercion due to mali-cious evasion from serving the applicable penalties.The purpose of the article is to identify the criteria for replacement of punishments to more severe one, including multi-stage replacement.Methodology. The author uses the method of analysis and synthesis, as well as formal legal method and dialectic approach.Results. The most vivid embodiment of the principle of the economy of repression is the provision of the courts the possibility of using alternative types of punishment that are al-ternative to deprivation of liberty (from fine to forced labor). Obviously, the economy of repression should be conditional.The economy of repression always involves a certain risk, which is, first of all, a threat to evade the convict who is serving the least repressive measure of influence. Consequently, the application of the most lenient repressive measure of state coercion must be compen-sated by the mechanism for ensuring its implementation.In the Criminal Code of the Russian Federation, the legislator uses different formulations that exclude a uniform solution to the question of a multi-step replacement of punishments.It requires a change in the provisions of federal laws that are not related to criminal law, as well as by-laws that transfer the replacement of punishment in the form of a fine and man-datory works with a more severe punishment from imperative to dispositive - contrary to the direct requirements of the criminal law.Conclusions. The legislative decision on the obligation of replacement should be clear and uniform. The current approach of the legislator is not justified, since the reality of replace-ment in determining the malicious evasion of the convicted person from serving the pun-ishment assigned to him should be the same regardless of the type of punishment served and should not become an automatic substitute, otherwise the court is deprived of the op-portunity to fully and comprehensively investigate the issue of the expediency of such a replacement in terms of the reasons for committing this violation of the regime and the achievement of the objectives of criminal punishment. Evasion of the convicted person from the sentenced punishment should always lead to neg-ative consequences for him, however, the institution of substitution of punishment for stricter ones does not meet this requirement.